Assessing provider and racial/ethnic variation in response to the FDA antidepressant box warning. (21st January 2019) - Cook, Benjamin L.; Wang, Ye; Sonik, Rajan; Busch, Susan; Carson, Nicholas; Progovac, Ana M.; Zaslavsky, Alan M.
Abstract : Introduction: After the 2004 FDA box warning raised concerns about increased suicidal ideation among youth taking antidepressants, antidepressant use decreased for White youth but slightly increased for Black and Latino youth. Better understanding of patient and provider factors contributing to these differences is needed to improve future risk warning dissemination. Methods: We analyzed antidepressant prescriptions for youth aged 5‐17 in 2002‐2006 Medicaid claims data from four states (CA, FL, NC, and NY). In multilevel models, we assessed provider‐ and patient‐level contributions to changes in antidepressant use by race/ethnicity and compared responses to the box warning between providers with large (>2/3) and small (<1/3) proportions of minority patients. Results: A significant amount of variance in overall prescribing patterns (calculated by the ICC) was explained at the provider level. Significant provider‐level variation was also identified in the differential effect of the box warning by racial/ethnic group. In a test of the influence of provider panel mix, we found that providers with large proportions of minority patients reduced antidepressant prescribing more slowly after the box warning than other providers. Discussion: This study is the first to assess provider‐ and patient‐level variation in the impact of a health care policy change on treatment disparities. Black and Latino youth Medicaid beneficiaries were seen by largely different providers than their White counterparts, and these distinct providers were influential in driving antidepressant prescription patterns following the box warning. Concerted outreach to providers of minority beneficiaries is needed to ensure that risk warnings and clinical innovations diffuse swiftly across racial/ethnic minority groups.